Perencanaan dan Penentuan Jadwal Induk Produksi di PT. Arwina Triguna Sejahtera - Sutoni, Akhmad; Siddiq, Muhammad Nasir (Jurnal Media Teknik dan Sistem Industri, 2017)
P.T. Arwina Triguna Sejahtera is a company engaged in the production of molding. Common issues in each company include P.T. Arwina Triguna Sejahtera, is experiencing constraints in planning the production amount according to production capacity. So planned to be created master production schedule so that the cost is not too high. Steps that are done is to start by doing data processing of the past by using demand aggregation, then do the forecasting in accordance with the characteristics of demand. Aggregate procurement planning is carried out for the next 1 (years) period using a permanent employment strategy. Then proceed at the disaggregation stage by using the proportion method, calculating the Master Production Schedule to find out how much quantity of product to produce, and when to start the production. Finally perform the calculation of Rought Cut Capacity Planning to know the balance between the available capacity and the required capacity. Production master schedule obtained, production will be smooth and able to meet the actual demand of 20,000 pcs by adding overtime hours and produce end items as much as 2.368 pcs for deabetamil scoop products, while for featherlock brown plastic products actual demand can be fulfilled. The feasibility of the master production schedule is calculated based on the suitability between Regular Man Hour on production plans, with the amount of time available in the calculated capacity capacity of 17,1360 hours to meet the demand for this year. Keywords— Production Controlling and Planning; Master Production Schedule; Agregate Production Planning; Rought Cut Capacity Planning; Production System.